2012
DOI: 10.1080/13548506.2011.651149
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of patients with amyotrophic lateral sclerosis

Abstract: The aim of this study is to evaluate the correlation between different measures of quality of life (QoL), functional status and mood status in patients with amyotrophic lateral sclerosis (ALS). A sample of 40 patients with ALS was recruited and scales for the evaluation of health-related QoL (SF36), patient-centered QoL (SEIQoL), functional status (ALSFRS) and depression (ZDS) have been administered to them. All the correlations (Pearson's r) between the scores have been considered and the t-test was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 30 publications
2
21
1
5
Order By: Relevance
“…Depression contributes to decreased quality of life in patients with ALS (Tramonti et al, 2012), however our study indicated that as a group patients with ALS were no more likely to be depressed than a HC population. Although these results are consistent with recent reports (Averill et al, 2007; Atassi et al, 2011) that claim prevalence rates of depression are low in ALS, our study was limited by a small sample size and was not representative of a valid prevalence-rate study.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Depression contributes to decreased quality of life in patients with ALS (Tramonti et al, 2012), however our study indicated that as a group patients with ALS were no more likely to be depressed than a HC population. Although these results are consistent with recent reports (Averill et al, 2007; Atassi et al, 2011) that claim prevalence rates of depression are low in ALS, our study was limited by a small sample size and was not representative of a valid prevalence-rate study.…”
Section: Discussioncontrasting
confidence: 61%
“…Like CI, research suggests that depressive symptoms in ALS may also have a negative impact on many aspects of quality of life (Tramonti et al, 2012), and could potentially affect cognition. To our knowledge however, no studies have examined the influence of depressive symptoms on cognitive performance in ALS.…”
Section: Introductionmentioning
confidence: 99%
“…At present, there is no cure and the only available drug (riluzole) prolongs the life of only a few months; therefore, the quality of life (QOL) changes are very useful in the meantime 2 . The interest in studying QOL of ALS patients has increased as recent studies have shown that alleviating symptoms and improving the QOL can affect the course of the disease and survival [2][3][4] . Besides, it is not obvious yet A C C E P T E D M A N U S C R I P T…”
Section: Introductionmentioning
confidence: 99%
“…De fato, o trabalho é uma parte importante da vida para a maioria dos adultos, e as fronteiras entre trabalho e outras esferas da vida são muito permeáveis, por exemplo, estado de humor e de satisfação no trabalho produz impactos no ambiente familiar e social [11][12][13][14].…”
Section: Discussionunclassified